Modeling and Parametric Study for Maximizing Heating Value of Gasification Syngas - Atnaw, Samson M.; Shaharin, A. Sulaiman; Singh, Lakhveer; Zularisam, A. W.; Wan Faizal, Wan Ishak (North Carolina State University, 2017)
There are a number of experimental and theoretical studies on the energy conversion of oil palm derivative biomass. Moreover, the potential of this abundant biomass residue for renewable energy in major producing countries in South east Asia has been well documented. In this study, the results of an equilibrium model of downdraft gasification of oil palm fronds (OPF), developed using the Aspen Plus chemical process simulator software, and its validation are presented. In addition, an optimization of the major output parameter of importance (i.e., the higher heating value of syngas) with respect to the main operating parameters (i.e.,temperature, equivalence ratio (ER), and moisture content) was performed. The response surface method (RSM) was used to determine the mathematical relation ship between the response of interest, which was the heating value of syngas, and the operating conditions. This method was used to further determine the conditions that would lead to optimum higher heating values of syngas. Optimum values identified by RSM were: oxidation zone temperature of 1000°C, moisture content in the range of 4%, and an equivalence ratio of 0.35. These optimum operating conditions and the corresponding higher heating value of syngas were found to correspond with the experimental results.